PERSPEKTIF POLITICAL JUSTICE DI DALAM IMPLEMENTASI BPJS PBI DI KOTA SURABAYA - Tamy Nur Nabilah; Kris Nugroho (Universitas Airlangga, 2020)
This study discusses the perspective of Political Justice in the Implementation of BPJS PBI in Surabaya. The study aims to determine the implementation of BPJS PBI in Surabaya has fulfilled Political Justice and the implementation of BPJS PBI in Surabaya is adequate as a form of political justice. The research method that uses is descriptive qualitative because it presents a detailed description of the situation or social phenomenon. Methods of data collection using direct interviews with resource persons include: Head of Surabaya City Health Office, Surabaya City DPRD Commission D, Lurah, PBJS recipient community. The results showed that the implementation of BPJS PBI in Surabaya City had not yet fulfilled Political Justice, based on indicators of fairness, equality, equality, and impartiality. The implementation of BPJS PBI in the city of Surabaya is also inadequate as a form of political justice because the state still determines justice in terms of profit and loss to health because the way of thinking lies in the amount of current contributions that do not match the actual calculation. Therefore, the implementation of the Health Insurance for the Poor program funded by the Surabaya City Regional Budget has not yet fulfilled the concept of Political Justice. This can be seen that there are still Health Insurance recipients who are not on target because of lack of accuracy in the process of verifying data on the poor in Surabaya, easy to get a Poor Certificate (SKM) that applies only once, and there are still groups of welfare recipients, so there is no meet the aspects of equity and justice.